Supplemental vitamins A, D, and E improve OPU-IVP efficiency in postpartum dairy cows by alleviating oxidative stress - Jinbang Xiao; Manyuan Tian; Zhengjie Ding; Haohao Mu; Haitao She; Heqiang Li; Bingke Wang; Hui Chen; Yonghong Jia; Yongsheng Wang; Yaping Jin; Pengfei Lin (Theriogenology, 2026)

Enhancing CO2 mineralization carbon sequestration of coal-based solid wastes through combined alkali activation and foam modification - Lei Qin; Dantong Li; Pengfei Liu; Miao Mu; Chengang Sun; Han Wang; Zengning Huang (Journal of Environmental Chemical Engineering, 2026)

GnRH supplementation in the PreOvsynch protocol targeting follicular cysts enhances synchronization and reduces days open in dairy cows - Jinbang Xiao; Manyuan Tian; Zhengjie Ding; Haohao Mu; Haitao She; Heqiang Li; Bingke Wang; Hui Chen; Yonghong Jia; Yongsheng Wang; Yaping Jin; Pengfei Lin (Animal Reproduction Science, 2026)

A physics-guided and scene-adaptive water index for consistent surface water mapping across regions and seasons - Shanchuan Guo; Pengfei Tang; Zilong Xia; Haowei Mu; Xiaoquan Pan; Peng Zhang; Yu Chen; Peijun Du (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Two decades of methane budgets at the sub-national scale in China - Pengfei Zhao; Zhen Zhang; Guanghui Huang; Zhenxuan Wang; Josep G. Canadell; Philippe Ciais; Huilin Chen; Shengqian Chen; Jason Blake Cohen; Fan Dai; Peng Gong; Robert B. Jackson; et al. (Science Bulletin, 2026)

Effect of early-age loading, formwork removal time, and curing method on the cracking behavior of hydraulic lining concrete structures: Experimental analysis and multi-scale coupling cracking analysis model - Pengfei Li; Haoyu Wang; Xuehui An; Duoyin Wang; Ping Mu; Feng Sheng (Tunnelling and Underground Space Technology, 2026)

Research progress in atmospheric haze chemistry: Formation mechanism of air pollution complex and control technologies - Qingxin Ma; Peng Zhang; Tianzeng Chen; Hao Li; Yonghong Wang; Jun Liu; Pengfei Liu; Yujing Mu; Jingjing Liu; Zhi Liu; Guangyan Xu; Yulong Shan; et al. (Journal of Environmental Sciences, 2026)

A weakly supervised approach for large-scale agricultural parcel extraction from VHR imagery via foundation models and adaptive noise correction - Wenpeng Zhao; Shanchuan Guo; Xueliang Zhang; Pengfei Tang; Xiaoquan Pan; Haowei Mu; Chenghan Yang; Zilong Xia; Zheng Wang; Jun Du; Peijun Du (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Strength and non-coaxiality behavior of warm frozen silt under inclined principal stress axes - Furong Liu; Wei Ma; Yanhu Mu; Zhi Wen; Mingde Shen; Pengfei He (Engineering Geology, 2026)

Characterization and source analysis of carbonyl compounds in a rural area of north China Plain: Results from 1-year continuous observations - Wenxin Cao; Xuran Li; Shuyang Xie; Jinyong Yang; Pengfei Liu; Chengtang Liu; Yuanyuan Zhang; Chenglong Zhang; Yujing Mu; Junfeng Liu (Atmospheric Pollution Research, 2026)

An improved open-top dynamic chambers method for measuring the exchange fluxes of N2O, NO and NH3 from farmland - Minhang Tan; Yining Hu; Yifei Song; Zixuan Huang; Yujing Mu; Junfeng Liu; Chenglong Zhang; Pengfei Liu; Yuanyuan Zhang (Journal of Environmental Sciences, 2026)

Effect of mixing and compaction methods on the physical properties, strength and microstructure of phase change material-modified soils under freeze-thaw process - Jun Bi; Yuxuan Pan; Wenxuan Mu; Mingyi Zhang; Guiyu Zhao; Haoxin Chen; Pengfei Liu (Cold Regions Science and Technology, 2025)

Emission fluxes of nitrous acid (HONO) from livestock and poultry wastes - Wenjin Zhang; Pengfei Liu; Min Song; Xuran Li; Xiaoxi Zhao; Yifei Song; Di Tian; Chenglong Zhang; Yuanyuan Zhang; Yangang Ren; Chengtang Liu; Junfeng Liu; et al. (Journal of Environmental Sciences, 2025)

NMR study on the distribution pattern of pore water in the process of freeze-thaw permeability enhancement of coal - Lei Qin; Pengfei Liu; Haifei Lin; Hui Wang; Ruizhe Wang; Miao Mu; Niandong Chen; Chengang Sun (Engineering Geology, 2025)

County-level coordination between urbanization and ecological change in dryland urban agglomerations: A quantitative approach based on remote sensing - Chunqiang Li; Shanchuan Guo; Zilong Xia; Xiaoquan Pan; Haowei Mu; Hong Fang; Pengfei Tang; Peijun Du (Journal of Geographical Sciences, 2025)

Hydroxyl-tunable type I photosensitizer based on curcumin for photodynamic therapy against hypoxic tumor cells - Yanping Wang; Tong Mu; Xuewei Li; Xiuli Zheng; Jie Sha; Zhe Yu; Yuanyuan Qin; Haohui Ren; Ying Wang; Weimin Liu; Pengfei Wang (Journal of Photochemistry and Photobiology B: Biology, 2025)

Evaluating the contribution of residential coal combustion to atmospheric nitrous acid (HONO) in winter - Yang Wang; Pengfei Liu; Chenglong Zhang; Chaoyang Xue; Xiaoxi Zhao; Shuang Fu; Zichen Wu; Yifei Song; Yuzheng Wang; Chengtang Liu; Yujing Mu (Environmental Pollution, 2025)

Synergistic cationic co-doping and electrolyte engineering enables stable anionic redox in P2-Type layered cathodes for sodium-ion batteries - Pengju Zhang; Jinglin Mu; Mingyu Xie; Tianyu Xue; Minghui Ding; Zhen Zhou; Junying Weng; Pengfei Zhou (Chemical Engineering Journal, 2025)

Recent advancements in observations, sources, and environmental effects of atmospheric hydrogen peroxide (H2O2) - Lian Duan; Shuyuan Jia; Xuran Li; Yalong Wang; Yiming Zhang; Shuang Fu; Yang Wang; Can Ye; Pengfei Liu; Zongbo Shi; Yujing Mu (Atmospheric Environment, 2025)

SLC39A10 is a key zinc transporter in T cells and its loss mitigates autoimmune disease - Yichang Shao; Qingdian Mu; Rong Wang; Hongbin Luo; Zijun Song; Pengfei Wang; Jingshu Song; Chaodong Ge; Jiyan Zhang; Junxia Min; Fudi Wang (Science China Life Sciences, 2025)

Application of natural mineral in round-the-clock solar-driven interfacial evaporation system: A review - Yunan Mu; Pengfei Shuai; Libing Liao; Xiaobin Gu (Journal of Environmental Chemical Engineering, 2025)

Composite electrolyte membrane with continuous Na+ transport for high-performance quasi-solid-state sodium batteries - Wenyong Yuan; Minghui Ding; Junying Weng; Tianyu Xue; Mingyu Xie; Pengju Zhang; Jinglin Mu; Pengfei Zhou (Chemical Engineering Journal, 2025)

Freeze–Thaw Response of Permeability and Absorption Channel Structure and Moisture Distribution in Different Coal Ranks - Lei Qin; Sinyin Lv; Shugang Li; Hui Wang; Pengfei Liu; Miao Mu; Jiawei Li (Natural Resources Research, 2025)

Changes in River Cross-section Morphology and Response to Streamflow and Sediment Processes in Middle Reaches of Yellow River, China - Yongfu Wen; Pengfei Li; Mengzhen Li; Chaohui Ma; Peng Gao; Xingmin Mu; Guangju Zhao (Chinese Geographical Science, 2025)

Moving in the landscape: Omnidirectional connectivity dynamics in China from 1985 to 2020 - Haowei Mu; Shanchuan Guo; Xingang Zhang; Bo Yuan; Zilong Xia; Pengfei Tang; Wei Zhang; Peng Zhang; Xuecao Li; Peijun Du (Environmental Impact Assessment Review, 2025)

Lycorine hydrochloride interferes with energy metabolism to inhibit chemoresistant glioblastoma multiforme cell growth through suppressing PDK3 - Qingsheng Dong; Wanxiang Niu; Maolin Mu; Chengkun Ye; Pengfei Wu; Shanshan Hu; Chaoshi Niu (Molecular and Cellular Biochemistry, 2025)

Annual emissions of N2O, NO, HONO, and NH3 from maize-wheat fields in the North China Plain - Yifei Song; Yuanyuan Zhang; Minhang Tan; Yining Hu; Pengfei Liu; Di Tian; Yujing Mu (Science of The Total Environment, 2024)

Fractal research on pores in oil and gas reservoirs - Inspirations from over 700 high pressure mercury injection experiments - Xingxing Kong; Hongjun Fan; Tingen Fan; Yufei Gao; Haifeng Wang; Pengfei Mu; Dianshi Xiao (Marine and Petroleum Geology, 2024)

Improvement of model simulation for summer PM2.5 and O3 through coupling with two new potential HONO sources in the North China Plain - Xiaoxi Zhao; Min Song; Xiujuan Zhao; Chaoyang Xue; Pengfei Liu; Can Ye; Xiaowei He; Yujing Mu; Bo Hu (Science of The Total Environment, 2024)

Functional characterization of large yellow croaker (Larimichthys crocea) Peroxiredoxin IV (PrxIV) gene promoter - Xianhui Wang; Pengfei Mu; Jieying Huo; Feng Han; Xinhua Chen; Jingqun Ao (Fish & Shellfish Immunology, 2024)

Effect of fertilizer deep placement and nitrification inhibitor on N2O, NO, HONO, and NH3 emissions from a maize field in the North China Plain - Yifei Song; Minhang Tan; Yuanyuan Zhang; Xuran Li; Pengfei Liu; Yujing Mu (Atmospheric Environment, 2024)

Exosomal circZNF800 Derived from Glioma Stem-like Cells Regulates Glioblastoma Tumorigenicity via the PIEZO1/Akt Axis - Ning Zhang; Pengfei Wu; Maolin Mu; Chaoshi Niu; Shanshan Hu (Molecular Neurobiology, 2024)
Exosomes play a crucial role in regulating crosstalk between tumor and tumor stem-like cells through their cargo molecules. Circular RNAs (circRNAs) have recently been demonstrated to be critical factors in tumorigenesis. This study focuses on the molecular mechanism by which circRNAs from glioma stem-like cell (GSLC) exosomes regulate glioblastoma (GBM) tumorigenicity. In this study, we validated that GSLC exosomes accelerated the malignant phenotype of GBM. Subsequently, we found that circZNF800 was highly expressed in GSLC exosomes and was negatively associated with GBM patients. CircZNF800 promoted GBM cell proliferation and migration and inhibited GBM cell apoptosis in vitro. Silencing circZNF800 could improve the GBM xenograft model survival rate. Mechanistic studies revealed that circZNF800 activated the PIEZO1/Akt signaling pathway by sponging miR-139-5p. CircZNF800 derived from GSLC exosomes promoted GBM cell tumorigenicity and predicted poor prognosis in GBM patients. CircZNF800 has the potential to serve as a promising target for further therapeutic exploration.

Formation Mechanism of NW-Trending Faults and Their Significance on Basin Evolution in Zhu III Depression of the Pearl River Mouth Basin, SE China - Pengfei Zhu; Lintao Zhao; Jiantai Zhang; Dunling Mu; Yichun Chen; Pengfei Rong (Journal of Marine Science and Engineering, 2024)
The Zhu III Depression, situated in the northern Pearl River Mouth Basin, features a complex fault system composed of NE–SW-, nearly E–W-, and NW–SE-oriented faults. However, there is limited research on NW-trending faults, especially regarding their formation mechanisms. Through structural analysis of 3D seismic profiles, we have revealed the geometric and kinematic characteristics of NW-trending faults and categorized them into three types based on their formation mechanisms: extensional fault, dextral transtensional fault, and sinistral strike–slip fault. The extensional faults predominantly developed as boundary faults during the rifting I period, caused by tectonic inversion of the NW–NWW-trending basement faults since early Eocene. The transtensional fault resulted from the dextral strike–slip motion of the NE-trending basin-controlling faults since late Eocene, under the regional dextral extension stress setting. The sinistral strike–slip faults have been dominant during the post-rifting period since early Oligocene. This is due to the sinistral shearing action related to the southeastward lateral extrusion of the Indochina Block and slab pull southward by subduction of the proto-SCS. The NW-trending faults controlled the development of local tectonics and structures, the depocenter migration during the rifting period, and the trapping, migration, and preservation of oil and gas.

Characteristics and sources of peroxyacetyl nitrate (PAN) in the rural North China Plain: Results from 1-year continuous observations - Xin Liu; Xiaowei He; Chenglong Zhang; Yifei Song; Shuyang Xie; Chengtang Liu; Pengfei Liu; Yuanyuan Zhang; Yujing Mu; Junfeng Liu (Journal of Environmental Sciences, 2024)

A comprehensive observation on the pollution characteristics of peroxyacetyl nitrate (PAN) in Beijing, China - Hailiang Zhang; Shengrui Tong; Wenqian Zhang; Yanyong Xu; Mingzhu Zhai; Yucong Guo; Xin Li; Lili Wang; Guiqian Tang; Zirui Liu; Bo Hu; Chengtang Liu; et al. (Science of The Total Environment, 2023)

Genome-Wide Identification of MYB Family Genes in Cerasus humilis Reveals Candidate Genes Involved in Flavonoid Biosynthesis - Xiaofang Xue; Hongbo Fu; Xiwen Guo; Jiancheng Zhang; Pengfei Wang; Xiaopeng Mu; Shuai Zhang; Junjie Du (Plant Molecular Biology Reporter, 2023)

The identification and expression of an interleukin-21 receptor in large yellow croaker (Larimichthys crocea) - Hanyu Wu; Qiuling Fu; Yan Teng; Pengfei Mu; Jingjie Chen; Xinhua Chen (Molecular Biology Reports, 2023)

Significantly mitigating PM2.5 pollution level via reduction of NOx emission during wintertime - Shuang Fu; Pengfei Liu; Xiaowei He; Yifei Song; Junfeng Liu; Chenglong Zhang; Yujing Mu (Science of The Total Environment, 2023)

Aging of pollution air parcels acts as the dominant source for nocturnal HONO - Wenjin Zhang; Yangang Ren; Chenglong Zhang; Pengfei Liu; Chaoyang Xue; Can Ye; Chengtang Liu; Jinhe Wang; Yuanyuan Zhang; Junfeng Liu; Yifei Song; Yinchang Feng; et al. (Science of The Total Environment, 2023)

Comprehensive analysis and identification of the circ_0084615/miR-451a/MEF2D axis in benzo(a)pyrene exposed tumor cells in hepato-carcinogenesis - Wei Mu; Pengfei Gu; Weiwei Song; Tengfei Zhu; Wenbo Wang; Yanfeng Zhou (Food and Chemical Toxicology, 2023)

A novel photochemical conversion technique for reliable calibration of peroxyacetyl nitrate (PAN) analyzers - Xiaowei He; Chenglong Zhang; Pengfei Liu; Gen Zhang; Hai Wu; Yuexiang Peng; Junfeng Liu; Chengtang Liu; Yujing Mu (Science of The Total Environment, 2023)

Atmospheric ammonia in the rural North China Plain during wintertime: Variations, sources, and implications for HONO heterogeneous formation - Pengfei Liu; Hui Chen; Yifei Song; Chaoyang Xue; Can Ye; Xiaoxi Zhao; Chenglong Zhang; Junfeng Liu; Yujing Mu (Science of The Total Environment, 2023)

Relationship between sediment load and climate extremes in the major Chinese rivers - Yatong Zhang; Peng Tian; Lin Yang; Guangju Zhao; Xingmin Mu; Bing Wang; Pengfei Du; Peng Gao; Wenyi Sun (Journal of Hydrology, 2023)

Large yellow croaker (Lrimichthys crocea) IL-2 modulates humoral immunity via the conserved JAK-STAT5 signal pathway - Pengfei Mu; Yan Teng; Hanyu Wu; Xinran Li; Jieying Huo; Jingqun Ao; Xinhua Chen (Fish & Shellfish Immunology, 2023)

Ambient volatile organic compounds in urban and industrial regions in Beijing: Characteristics, source apportionment, secondary transformation and health risk assessment - Chengtang Liu; Yanyan Xin; Chenglong Zhang; Junfeng Liu; Pengfei Liu; Xiaowei He; Yujing Mu (Science of The Total Environment, 2023)

Genome-Wide Identification and Expression Analysis of AAAP Gene Family in Cerasus humilis During Fruit Development - Hongbo Fu; Pengfei Wang; Junjie Du; Xiaopeng Mu; Shengyong Yuan; Yongchao Yang; Jie Li (Plant Molecular Biology Reporter, 2022)

Quick mapping and characterization of a co-located kernel length and thousand-kernel weight-related QTL in wheat - Xiangru Qu; Cong Li; Hang Liu; Jiajun Liu; Wei Luo; Qiang Xu; Huaping Tang; Yang Mu; Mei Deng; Zhien Pu; Jun Ma; Qiantao Jiang; et al. (Theoretical and Applied Genetics, 2022)

Variations of pan evaporation and its attribution from 1961 to 2015 on the Loess Plateau, China - Jinfei Hu; Guangju Zhao; Pengfei Li; Xingmin Mu (Natural Hazards, 2022)

Characterization and fine mapping of a lesion mimic mutant (Lm5) with enhanced stripe rust and powdery mildew resistance in bread wheat (Triticum aestivum L.) - Cong Li; Hang Liu; Jian Wang; Qi Pan; Yue Wang; Kunyan Wu; Peiying Jia; Yang Mu; Huaping Tang; Qiang Xu; Qiantao Jiang; Yaxi Liu; et al. (Theoretical and Applied Genetics, 2022)

Development of Recombinant Dihydrolipoamide Dehydrogenase Subunit Vaccine against Vibrio Infection in Large Yellow Croaker - Xiaomeng Li; Yuanzhen Tan; Zheng Zhang; Yupeng Huang; Pengfei Mu; Zhengwei Cui; Xinhua Chen (Fishes, 2022)
Large yellow croaker (Larimichthys crocea), an economically important marine fish in China, has suffered from serious vibriosis, which has resulted in great economic losses for the large yellow croaker industry. Vaccination has been considered to be a safe and effective method to prevent and control vibriosis. However, due to the complex diversity and serotypes of the Vibrio genus, the progress of Vibrio vaccine development is still slow. In this study, we prepared recombinant Vibrio dihydrolipoamide dehydrogenase (rDLD) protein and investigated its potential as a candidate to be a subunit vaccine against Vibrio. The lysozyme activity and the rDLD-specific antibody level in sera of large yellow croakers immunized with rDLD were significantly higher than those in the control group, and the transcript levels of proinflammatory cytokines (IL-6, IL-8, IL-1β), MHC IIα/β, CD40, CD8α, IL-4/13A, and IL-4/13B were significantly up-regulated in the spleen and head kidney of large yellow croakers immunized with rDLD, suggesting that rDLD could induce both specific and nonspecific immune responses in this species. In addition, rDLD protein increased the survival rate of large yellow croakers against Vibrio alginolyticus and Vibrio parahaemolyticus, with the relative percent of survival (RPS) being 74.5% and 66.9%, respectively. These results will facilitate the development of a potential subunit vaccine against Vibrio in large yellow croaker aquaculture.

QTL mapping and validation of bread wheat flag leaf morphology across multiple environments in different genetic backgrounds - Yang Tu; Hang Liu; Jiajun Liu; Huaping Tang; Yang Mu; Mei Deng; Qiantao Jiang; Yaxi Liu; Guoyue Chen; Jirui Wang; Pengfei Qi; Zhien Pu; et al. (Theoretical and Applied Genetics, 2021)

A novel, validated, and plant height-independent QTL for spike extension length is associated with yield-related traits in wheat - Cong Li; Huaping Tang; Wei Luo; Xuemei Zhang; Yang Mu; Mei Deng; Yaxi Liu; Qiantao Jiang; Guoyue Chen; Jirui Wang; Pengfei Qi; Zhien Pu; et al. (Theoretical and Applied Genetics, 2020)

Correction to: Identification and validation of a major and stably expressed QTL for spikelet number per spike in bread wheat - Jian Ma; Puyang Ding; Jiajun Liu; Ting Li; Yaya Zou; Ahsan Habib; Yang Mu; Huaping Tang; Qiantao Jiang; Yaxi Liu; Guoyue Chen; Jirui Wang; et al. (Theoretical and Applied Genetics, 2020)

Identification and validation of a major and stably expressed QTL for spikelet number per spike in bread wheat - Jian Ma; Puyang Ding; Jiajun Liu; Ting Li; Yaya Zou; Ahsan Habib; Yang Mu; Huaping Tang; Qiantao Jiang; Yaxi Liu; Guoyue Chen; Jirui Wang; et al. (Theoretical and Applied Genetics, 2019)

Identification and validation of a novel major QTL for all-stage stripe rust resistance on 1BL in the winter wheat line 20828 - Jian Ma; Nana Qin; Ben Cai; Guoyue Chen; Puyang Ding; Han Zhang; Congcong Yang; Lin Huang; Yang Mu; Huaping Tang; Yaxi Liu; Jirui Wang; et al. (Theoretical and Applied Genetics, 2019)

Effects of climate change and human activities on runoff and sediment inputs of the largest freshwater lake in China, Poyang Lake - Chaojun Gu; Xingmin Mu; Peng Gao; Guangju Zhao; Wenyi Sun; Pengfei Li (Hydrological Sciences Journal, 2017)

Changes in daily and monthly rainfall in the Middle Yellow River, China - Yi He; Peng Tian; Xingmin Mu; Peng Gao; Guangju Zhao; Fei Wang; Pengfei Li (Theoretical and Applied Climatology, 2017)

F-box Protein Arabidillo-1 Promotes Lateral Root Development by Depressing the Functioning of GA3 in Arabidopsis - Changjun Mu; Ni Chen; Xiaofeng Li; Pengfei Jia; Zhaoyan Wang; Heng Liu (Journal of Plant Biology, 2010)

Convective scale structure and evolution of a squall line observed by C-band dual Doppler radar in an arid region of northwestern China - Liping Liu; Wei Zhuang; Pengfei Zhang; Rong Mu (Advances in Atmospheric Sciences, 2010)